Ruptured caesarean scar ectopic pregnancy - Saiyyed, Anjum (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Caesarean scar ectopic is a rare form of ectopic whose incidence has been on rise recently due to increase in incidence of caesarean section. In 1972 the first report of scar ectopic was reported in medical literature. It is a type of abnormal implantation in a scarred uterus following surgery most commonly caesarean section. Early diagnosis and management is the key to prevent morbidity and mortality. Here we present a case of gravida 3 para 2 with previous 2 LSCS with ruptured caesarean scar ectopic with massive haemorrhage. Timely resuscitation and laparotomy helped prevent morbidity and mortality in this patient.